The Role of Technology in Music Education: A Survey of Computer Usage in Teaching Music in Colleges of Education in The Volta Region, Ghana - Foster Mawusi, Eddison; Kwadwo, Klutse Eric (International Journal of Scientific Research and Management (IJSRM), 2020)
The study sought to find out the role of computer technology in music education in Colleges of Education in the Volta Region of Ghana. It aimed at surveying the use of computer technology for teaching music and exploring the instructional prospects for computer technology usage in music in Colleges of Education. The study employed Rogers’ Diffusion Innovation theory and descriptive survey research method. Data was collected from the respondents using questionnaire, interview, and observation. The study revealed that even though about 90% of the music tutors have good academic qualification and over five years teaching experience, lack of competence in handling computer technology in teaching music among some music tutors and incoherent ICT initiatives hindered proper application of computer technology in the field of music education. It is however envisaged that increasing access and coherent computer technology initiatives will be paramount for the teaching of music in the Colleges of Education.